Global Affordable Housing Challenges - Oyamo, Rumanor; Migel Oyatomu, Jay (one million dreams corporation, 2025)
The issue of affordable housing has become a global challenge with far-reaching economic, social, and environmental implications. Despite efforts by both the public and private sectors, the impact has not been significant in addressing the housing crisis that is occurring in various parts of the world. In response, public-private partnerships (PPPs) are increasingly being promoted as a strategic solution. This study aims to evaluate the key factors that influence the effectiveness of PPPs in providing affordable housing, while analyzing the limitations of the “universal solution” approach in diverse contexts. The findings show that while financing practices, land regulations, and community income levels play an important role, the success of PPPs also depends heavily on appropriate risk allocation, socio-political stability, and regulatory quality standards. Thus, while PPPs offer potential solutions, their implementation must be tailored to the specific conditions of each region to ensure optimal outcomes.